2018
DOI: 10.2991/j.jegh.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance: Awareness, Utilization, and its Determinants among the Urban Poor in Delhi, India

Abstract: This study reports the awareness, access, and utilization of health insurance by the urban poor in Delhi, India. The study included 2998 households from 85 urban clusters spread across Delhi. The data were collected through a pretested, intervieweradministered questionnaire. Logistic regression was performed for determinants of health insurance possession. Only 19% knew about health insurance; 18% had health insurance (Employees State Insurance Scheme-ESIS-8%; Central Government Health Scheme-CGHS-1.4%; Rashtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 23 publications
3
36
1
Order By: Relevance
“…Unfortunately, there is little awareness and complete ignorance towards such schemes among the majority population (poor and middle class) of Pakistan. Consequently, this reduces the community's' willingness to spend on CBHIS (8,9). This underscores the need for governmental policymakers and other researchers to key into the findings of the present study and create more community awareness, stakeholder sensitization and eventually stimulates commencement of CBHIS as per demand in the country (10).…”
Section: Introductionmentioning
confidence: 78%
“…Unfortunately, there is little awareness and complete ignorance towards such schemes among the majority population (poor and middle class) of Pakistan. Consequently, this reduces the community's' willingness to spend on CBHIS (8,9). This underscores the need for governmental policymakers and other researchers to key into the findings of the present study and create more community awareness, stakeholder sensitization and eventually stimulates commencement of CBHIS as per demand in the country (10).…”
Section: Introductionmentioning
confidence: 78%
“…[ 17 ] In our study, 80.8% were covered under some form of health insurance scheme with a majority, 97.9%, being enrolled to RSBY, which is greater than other parts of India. [ 18 19 ] Studies show that major factors contributing to poor coverage were found to be lack of awareness and political will. [ 17 20 ] It was found that only 5.8% were totally unaware of any health insurance schemes in this study population.…”
Section: Discussionmentioning
confidence: 99%
“…For these remote localities, it may be cost-effective to go to a nearby facility and pay out of pocket. Distance to the empanelled healthcare facility was found to be significant to utilization in several other global studies (Iqbal et al, 2017;Kusuma, Pal, & Babu, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…All this fall under the 'awareness creation' umbrella that was not strongly and frequently linked with the scheme from the start. Employees State Insurance Corporation health camps at Bengaluru, India, suggest that repeated interaction with the community work to establish trust and develop understanding of the benefits of the scheme (Kusuma, Pal, & Babu, 2018;Nagaraja et al, 2013).…”
Section: Discussionmentioning
confidence: 99%